Euthanasia in the case of dementia: a survey among Flemish GPs - Cleemput, Jasper (BJGP Open, 2019)
BACKGROUND: In Belgium law prohibits euthanasia at the end stage of dementia when patients are no longer able to formulate their will. The number of applications for euthanasia based on dementia is low, but patients and their relatives are searching for access to euthanasia. AIM: This study assessed the opinions of GPs facing requests for euthanasia in patients with dementia. DESIGN & SETTING: A cross-sectional survey was performed in general practice. Flemish GPs were invited by email to participate in the study. METHOD: GPs were reached through the regional GP association and the online survey was open for 4 weeks. The data were then anonymised, analysed, and interpreted. The outcome of interest addresses opinions of Flemish GPs regarding euthanasia in patients with dementia. RESULTS: A total of 113/308 doctors participated. It was found that 69% agreed that euthanasia in patients without dementia is more acceptable than in patients with dementia. When patients with dementia had concomitant diseases, 59% stated that euthanasia was more acceptable than when patients were ‘healthy’. It was also found that 56% agreed the euthanasia law needs adjustments towards patients with dementia. Legal adjustments were supported more by GPs of a younger generation. Non-religious doctors were twice as likely to be in favour of legal adjustments than their religious colleagues; 51% believed that the ability of patients to repeat their will is essential; while 72% of GPs feared pressure from relatives to follow the declaration of will. CONCLUSION: The Belgian GP has an open attitude towards euthanasia for patients with dementia. There was a willingness to perform euthanasia as the stage of dementia worsened and in cases of terminal conditions. Debate, education, and experience will influence opinion and the legislation process.